2017
DOI: 10.1161/circulationaha.117.029986
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Cardiac Troponin T Elevations in Chronic Kidney Disease

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 5 publications
0
20
1
2
Order By: Relevance
“…Lastly, a recent study from our group showed that impaired renal clearance is not the main driver behind persistently increased cardiac troponin concentrations (8). Although the results presented here may seem to be at odds with that conclusion, it is important to consider that the current study demonstrated that cardiac troponin in urine is limited to AMI patients with high cTnT concentrations in serum (>1000 ng/L) and concomitant proteinuria.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Lastly, a recent study from our group showed that impaired renal clearance is not the main driver behind persistently increased cardiac troponin concentrations (8). Although the results presented here may seem to be at odds with that conclusion, it is important to consider that the current study demonstrated that cardiac troponin in urine is limited to AMI patients with high cTnT concentrations in serum (>1000 ng/L) and concomitant proteinuria.…”
Section: Discussioncontrasting
confidence: 54%
“…Nevertheless, the interpretation of cardiac troponin concentrations can be challenging, especially in individuals with persistently increased levels (4,5), like those found in chronic kidney disease patients. The high prevalence of persistently increased cardiac troponin concentrations among individuals with impaired renal function has raised the question if, and if so how, the kidneys are involved in the terminal elimination of cardiac troponins (6)(7)(8). A better understanding of the final elimination of cardiac troponins might help us better interpret cardiac troponin concentrations.…”
mentioning
confidence: 99%
“…Although renal function did affect the level of natriuretic peptides and troponin, eGFR did not appear to be the major determinant of these cardiac biomarker levels (22). Recent data showed similar diurnal variation in patients with and without chronic kidney disease, which suggested that decreased clearance is not the primary mechanism for elevated high-sensitivity cardiac troponin levels in the patients with renal failure (23). Importantly, elevated levels of natriuretic peptides and troponin were associated in many studies with cardiovascular events and outcome 24, 25.…”
Section: Discussionmentioning
confidence: 98%
“…Lastly, postoperative cTn elevations may also occur in the presence of acute and chronic kidney disease and injury. Whilst a recent study showed that the origin of cTnT elevations in chronic kidney disease is overwhelmingly cardiac and not impaired renal elimination, 26 this is not clear in acute kidney injury, where impaired renal elimination may be the dominant cause.…”
Section: Discussionmentioning
confidence: 99%